Impact of Seasonal Changes on Water Characterstics at Palakkad in 2021-2022 - Jayakrishnan R; M, Gopika; R, Miduna; Vishnu T P (International Journal of Engineering and Management Research, 2022)
Geometric increase in population coupled with rapid urbanization, industrialization and agricultural development has resulted in high impact on quality and quantity of water in India. Hence, the availability and the quality of the freshwater resources are the most pressing of the many environmental challenges in India (CPCB 2011). The quality of water is of vital concern for mankind, since it is directly linked with human welfare. Poor quality of water adversely affects the plant growth and human health (WHO 1984; Hem 1985). A number of studies on water quality have been carried out in different parts of India All these studies reveal that both rivers and groundwater in India are facing water quality issues. The state of Kerala, located in the south-western corner of India, is blessed with 44 rivers and heavy rainfall of 3000 mm/year. However, most of the water in the rivers is quickly drained into the Arabian Sea due to the steep seaward sloping of the state. Hence, in addition to rivers, the groundwater is also utilized to meet the water requirements of the state. The increase in population, development activities, urbanization, change in land-use pattern, etc. has created a concern among the people of Kerala regarding both the river water and groundwater quality of various river basins.